Exploring hygiene practices, prenatal recommendations and parental attitudes towards congenital cytomegalovirus prevention and screening in Sweden - Allison Mackey; Ulrika Löfkvist (BMJ Paediatrics Open)
Objective The aims of the study were to explore the attitudes of parents of young children towards prevention and screening for congenital cytomegalovirus infection, and to map the practices and recommendations in prenatal care regarding the prevention of fetal infection.Methods A survey was distributed across Sweden to parents of children under 2 years. Information about congenital cytomegalovirus infection was provided. Questions followed, pertaining to attitudes towards screening and prevention, hygiene behaviours during pregnancy, and recommendations from midwives.Results 4405 parents completed the survey; 4263 were pregnant less than 2 years prior. Parents were positive towards screening, with 85% agreeing that screening should be offered. A predicted increase in stress was positively associated with positive attitudes towards screening. Attitudes towards prevention were positive (90%). Most did not regularly perform hygiene measures to prevent cytomegalovirus infection during pregnancy, though behaviours preventing other infections were common. Recommendations by midwives rarely included cytomegalovirus prevention.Conclusion Parents have positive attitudes toward screening and prevention of congenital cytomegalovirus infection, despite a predicted increase in stress. Information is not being conveyed by prenatal providers about how to protect oneself against cytomegalovirus infection, which reflects a lack of hygiene routines during pregnancy related to its prevention.